Cơ sở dữ liệu quan hệ với giá trị null phụ thuộc vào ngữ cảnh - Hiền, Bùi Thị Thúy (Journal of Computer Science and Cybernetics, 2016)
We propose a new approach to the treatment of null valued attributes in the relational model. The approach is based on the comment: "Every null value is defined by the data context in which it appears in the database". With each null value we define it's data context and call it as context dependent null value. It is shown that in our approach the user can obtain more information related to null values from database systems than in the usual case.